Synthesis of phosphorus/nitrogen containing intumescent flame retardants from p-hydroxybenzaldehyde, vanillin and syringaldehyde for rigid polyurethane foams. (January 2022) - Lu, Weimiao; Jin, Zhenfu
Highlights: Intumescent flame retardants (IFR) with phosphorus/nitrogen-containing diphenols (DH, DV and DS) were synthesized successfully from p -hydroxybenzaldehyde (H), vanillin (V) and syringaldehyde (S) with different methoxyl groups on its aromatic ring. The phosphorus/nitrogen-containing diphenols DH, DV and DS were good flame retardant additives and exhibited effective role of reducing fire hazard between gaseous and condensed phases, thus enhanced the flame retardancy and thermal stability properties for rigid polyurethane foams. The efficiency of three intumescent flame retardants DH, DV and DS were different and the best flame retardancy and thermal stability was obtained from RPU-DS foam. Abstract: Intumescent flame retardants (IFR) with phosphorus (P)/nitrogen (N)-containing diphenols (DH, DV and DS) were synthesized from p -hydroxybenzaldehyde (H), vanillin (V) and syringaldehyde (S) with different methoxyl groups on its aromatic ring. The FTIR, 1 H NMR, 13 C NMR, XPS methods were used to characterize the structures of IFR, and LOI, CCT, SEM, TG methods were used to investigate the flame retardancy and thermal stability of rigid polyurethane (RPU) foams when the three IFR were incorporated into RPU foams. Compared with H, V and S, the DH, DV and DS FTIR spectra showed absorption peaks at 3450 cm −1, 1160 cm −1, and 1222 cm −1, 1050 cm −1 and 740 cm −1, respectively, which attributed to NH, CN, and P  =  O, P-O, P-C groups. The 1 H NMR spectra of DH, DV and DS showed proton signals at 4.8 and 6.0 ppm, which were corresponding to H1 and H2 of CN groups, and corresponding C1 signal appeared around 62.3 ppm in the 13 C NMR spectra. The XPS spectra of DH, DV, DS showed peaks at 285, 398 eV and 133.5, 532 eV, which may be due to corresponding C1s, N1s of CN groups and P2p and O1s of P-O-C groups, respectively. These results indicated that the target compounds P/N-containing diphenols DH, DV and DS were synthesized successfully. Flame retardancy index (FRI) values of RPU-DH, RPU-DV, and RPU-DS were 2.33, 2.30 and 2.43, respectively, suggesting that DH, DV, and DS were good flame retardant additives. The THR and HRR values of RPU-DH, RPU-DV, RPU-DS foams were much lower than that of RPU foam. The fire growth rate (FIGRA) of RPU-DH, RPU-DV, and RPU-DS was 29.4%, 30.3%, and 24.4% lower comparing to RPU foam. The LOI value of RPU foam was 19%, while LOI values of RPU-DH, RPU-DV and RPU-DS foams increased to around 26%. These results suggested that the flame retardancy of RPU foams were improved by incorporating DH, DV, and DS. Compared with RPU foam, the CY600 of RPU-DH, RPU-DV and RPU-DS foams increased by 215.2%, 152.2% and 195.6%, respectively, and the char residue after CCT were much compact and homogeneous, which could reduce heat and mass transfer, protecting underlying materials from further combustion in a fire. In conclusion, the P/N-containing diphenols DH, DV and DS were synthesized successfully, and they were good flame retardant additives. The char residue of RPU-DH, RPU-DV and RPU-DS foams increased remarkably, and formed compact and homogeneous char layer. The flame retardancy and thermal stability of RPU-DH, RPU-DV, RPU-DS foams were improved by incorporating DH, DV, and DS.